Dysregulation of Mesenchymal Stromal Cell Antioxidant Responses in Progressive Multiple Sclerosis. (31st July 2018) - Redondo, Juliana; Sarkar, Pamela; Kemp, Kevin; Heesom, Kate J; Wilkins, Alastair; Scolding, Neil J; Rice, Claire M
Abstract : The potential of autologous cell-based therapies including those using multipotent mesenchymal stromal cells (MSCs) is being investigated for multiple sclerosis (MS) and other neurological conditions. However, the phenotype of MSC in neurological diseases has not been fully characterized. We have previously shown that MSC isolated from patients with progressive MS (MS-MSC) have reduced expansion potential, premature senescence, and reduced neuroprotective potential in vitro. In view of the role of antioxidants in ageing and neuroprotection, we examined the antioxidant capacity of MS-MSC demonstrating that MS-MSC secretion of antioxidants superoxide dismutase 1 (SOD1) and glutathione S-transferase P (GSTP) is reduced and correlates negatively with the duration of progressive phase of MS. We confirmed reduced expression of SOD1 and GSTP by MS-MSC along with reduced activity of SOD and GST and, to examine the antioxidant capacity of MS-MSC under conditions of nitrosative stress, we established an in vitro cell survival assay using nitric oxide-induced cell death. MS-MSC displayed differential susceptibility to nitrosative stress with accelerated senescence and greater decline in expression of SOD1 and GSTP in keeping with reduced expression of master regulators of antioxidant responses nuclear factor erythroid 2-related factor 2 and peroxisome proliferator-activated receptor gamma coactivator 1-α. Our results are compatible with dysregulation of antioxidant responses in MS-MSC and have significant implications for development of autologous MSC-based therapies for MS, optimization of which may require that these functional deficits are reversed. Furthermore, improved understanding of the underlying mechanisms may yield novel insights into MS pathophysiology and biomarker identification.